MORAL PAJAK, EGOISME WAJIB PAJAK, DAN PENGHINDARAN PAJAK - Hidayatulloh, Amir; Khasanah, Uswatun; Fikrianoor, Kahfi (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
This research aims to analyze the influence of tax morals and taxpayers on tax avoidance. Apart from that, this research also aims to analyze the influence of tax morals on tax avoidance with the mediating variable taxpayer egoism. Data collection was carried out by distributing questionnaires to respondents. The sample for this research is individual taxpayers in Indonesia who have a NPWP. The number of respondents to this research was 350 respondents from 11 provinces in Indonesia. This research data analysis uses Partial Least Square with the help of the WarpPLS tool. This research obtained results that tax morals, taxpayer egoism influence tax avoidance. Apart from that, this research also obtained results that the influence of tax morals on tax avoidance is not mediated by taxpayer egoism.